Pentingnya Perjanjian Kerjasama dalam Bisnis yang Memiliki Kekuatan Mengikat secara Hukum - Bella Monica Rahma Hamida; Risma Dewi Hermawan (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
A covenant is an event in which one person promises to another or in which two people promise each other to do something. The purpose of this community service is to add information about the benefits of the agreement, add information about laws related to the agreement, and add information about the function of the cooperation agreement. With a better understanding of legal capacity, people can make legal and binding agreements and contracts, and understand the legal consequences that may arise from such agreements or contracts. Improving public understanding of the role of legal capacity in agreements and contracts is a key step in realizing legal certainty and Justice. The results of the dedication and discussion contain data collection, the length of time for carrying out activitie, and data analysis. The results of the data analysis are completed with a detailed discussion instead of raw data, a review of the relationship between the results and basic concepts, and or hypothesis testing results.